India's Increasing Skill Premium : Role of Demand and Supply - Azam, Mehtabul (2012)
Using micro data for India from 1983 to 2005, this paper finds that the tertiary (college)-secondary (high school) wage premium has been increasing in India over the past decade and that this increase differs across age groups. The increase in wage premiums has been driven mostly by younger age groups while older age groups have not experienced any significant increase. Using a demand and supply model with imperfect substitution across age groups (developed in Card and Lemieux, 2001), this paper demonstrates that workers are not perfect substitutes across age groups. The paper finds that the increase in the wage premium has come mostly from demand shifts in favor of workers with a tertiary education. More importantly, the growth rate of demand for tertiary educated workers relative to secondary educated workers was fairly stable in the 1980s and the 1990s. However, the relative supply played an important role not only in determining the extent of increase in wage premium, but also its timing. The increase in relative supply of tertiary workers during 1983-1993 negated the demand shift; as a result, the wage premium did not increase much. But during 1993-1999, the growth rate of the relative supply of tertiary workers decelerated, while relative supply became virtually stagnant during 1999-2004. Both these periods saw an increase in the wage premium as the countervailing supply shift was weak.